2022
DOI: 10.1007/s11869-022-01278-w
|View full text |Cite
|
Sign up to set email alerts
|

Radon levels and indoor air quality after application of thermal retrofit measures—a case study

Abstract: This study was conducted to evaluate the influence of thermal retrofit on radon levels in workrooms, and to determine whether the radon concentration in the building changes after the application of retrofit measures. In the first survey, digital Airthings Corentium Home radon detector was used for 1-month radon measurements during the heating season 2018/19. The daily averaged radon concentrations varied from 37 to 573 Bq/m 3 for 10 selected workrooms, while hourly averaged radon measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These might be the probable reasons for having lower Rn levels obtained in our study. Studies [41][42][43] clarified similar influences of ventilation, usage of mechanical appliances, and building factors affecting indoor Rn reduction/variation. On the other hand, obtained long-term Tn concentration (7 ± 2 Bqm −3 to 56 ± 8 Bqm −3 ) was higher than Rn (Table 1).…”
Section: Estimation Of Indoor Radon and Thoron Concentrations In Dwel...mentioning
confidence: 98%
“…These might be the probable reasons for having lower Rn levels obtained in our study. Studies [41][42][43] clarified similar influences of ventilation, usage of mechanical appliances, and building factors affecting indoor Rn reduction/variation. On the other hand, obtained long-term Tn concentration (7 ± 2 Bqm −3 to 56 ± 8 Bqm −3 ) was higher than Rn (Table 1).…”
Section: Estimation Of Indoor Radon and Thoron Concentrations In Dwel...mentioning
confidence: 98%
“…Precautions that can be taken to reduce the risks and hazards caused by radon are given below [20,28,57,121,[146][147][148][149][150][151][152]:…”
Section: Possible Precautions Against Radonmentioning
confidence: 99%
“…The implementation of energy-saving measures can improve the indoor air quality. However, some authors reported that leak-proof PVC windows lead to increased radon accumulation, so the controlled ventilation system should be applied in the lowermost floor of building [51,52].…”
Section: Mitigation Measuresmentioning
confidence: 99%